Misconceptions about Science Learning Materials of Class V in Elementary Schools using A Diagnostic Instrument of Four-Tier Multiple Choice - Atmojo, Idam Ragil Widianto; Saputri, Dwi Yuniasih; Fadhilah, Alfianita Nur (Jurnal Pendidikan dan Pengajaran, 2024)
The current Indonesian education system requires a comprehensive assessment of students which is summarized in three major aspects: cognitive, psychomotor, and affective. Assessments are carried out to measure the achievement of expected learning indicators and identify learning difficulties. Teachers must know their students' learning difficulties and misconceptions, so appropriate steps can be taken to overcome the problems. One of the solutions is carrying out diagnostic tests. This research aimed to analyze misconceptions about science learning materials in theme VI concerning heat and its transfer to class V of elementary schools. This research was conducted using a qualitative approach. The data collection method was a four-tier diagnostic test and interviews. The sampling technique used purposive sampling, namely all the fifth graders of public elementary school (SDN) 1 Krasak, Boyolali. The research results showed that the average misconception occurring among students was 29.33% which belonged to the low category. The lowest misconception with a percentage of 23.32% was in the sub-concept of conductors and insulators. The highest misconception was in the sub-concept of differences in temperature and heat with a percentage of 36.65%. Factors that caused misconceptions among students were wrong preconceptions, low interest in learning, and inappropriate reasoning.